Banking sector of Spain: innovation - T. Malashenko (Ибероамериканские тетради, 2019)
In a turbulent global economy, the introduction of innovations in the banking sector is a key factor in improving efficiency and stabilizing the global financial system. World financial and economic crisis of 2008-2009 became a serious test for the economy of Spain. The recognition of the importance of adapting the banking sector to new economic conditions is becoming increasingly relevant for considering modern processes taking place in the European Union and in the global economy as a whole. Spain is at the forefront in introducing digital technology into the banking sector, but its experience has been little studied. This is the first work analyzing the Spanish experience in introducing, developing and operating new technologies: Blockchain, mobile banking applications, alternative finance, sharing platforms, crowdsourcing. The author concludes that the introduction of innovation has transformed the banking sector in Spain and has led to a decrease in bank employees and a reduction in offices. The freed up resources were directed to the activation of the digital segment, which led to the leading position of Spain in digital banking. In the future, an even greater spread and development of these technologies is expected. It will grow more slowly than income, as deferred demand is absorbed and households increase their savings rates.